PENERAPAN MODEL PROBLEM SOLVING DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI KELAS XI SMA NEGERI 3 DENPASAR - Praningsih, Niluh Ayu; Winanti, Ni Putu; Prabawati Kusuma Dewi, Ni Wayan (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2023)
Education is one of the important things in determining the progress and decline of a nation, Learning Capital plays an important role in the morale of Education, The learning model determines the goals of Education at SMA Negeri 3 Denpasar has implemented the Problem Solving Model in learning Religious Education, especially Hindu Religious Education and Good Morals which worthy of scrutiny. The formulation of the problems applied include: This study describes the form of implementation of learning activities by applying the Problem Solving Model in the Application of the Problem Solving Learning Model in Learning Hindu Religious Education and Characteristics in class XI SMA Negeri 3 Denpasar. teacher's efforts in applying the Problem Solving Model in Hindu Religious Education and Moral Education Learning in class XI SMA Negeri 3 Denpasar. the impact of the application of the Problem Solving Model in Hindu Religion and Moral Learning in class XI SMA Negeri 3 Denpasar. The theory used in this study is: constructivism, Behavioristic. This type of research is case study research while collecting data using several techniques or methods, namely: observation, interviews, documentation, literature study. The results of the researchers showed that: (1) The implementation of problem solving model learning in learning Hindu Religion and Moral Education includes: planning, implementing and reflecting on learning. (2) The teacher's efforts in applying the problem solving model are a learning process that is used in SMA Negeri 3 Denpasar. In this application, there are several efforts made by the teacher, the efforts made are: Efforts to apply technology in the learning process and prepare learning media that sufficient, and solve problems by forming small groups. (3) The impact or implicit of the Problem Solving Model in learning Hindu Religious Education and Character increases student learning motivation and improves student learning outcomes. It has an impact on teachers, students and schools. It is this impact that will provide responses and learning outcomes for students and teachers when This learning process takes place in the classroom with this Problem Solving Model.